Leveraging optical spectrophotometry for outstanding malaria diagnosis - Baptista, Vitória Cunha (2024)
The use of prompt and highly sensitive point-of-care malaria testing is a crucial piece of the puzzle to support its elimination. Unfortunately, the effectiveness of the current diagnostic methods, either optical or rapid diagnostic tests (RDTs), is limited, leaving room for improvements. Hemozoin, a by-product of hemoglobin human infected red blood cells (RBCs), has emerged as an outstanding malaria biomarker. Along the inside RBCs, the dynamic relationship between hemoglobin and hemozoin proportions originates distinct healthy and infected samples. Therefore, herein, optical spectrophotometry is explored for the detection of low-level Plasmodium falciparum infections based on hemozoin. Specifically, we characterize the optical spectra of healthy and P. falciparum-infected samples. Moreover, we simulate optical filters and design, simulate, and fabricate an optical detection microsystem, aiming their integration in a malaria diagnostic device. For samples characterization, a 200 W Halogen source directed light onto the sample and the transmitted or reflected light was detected on a top-bench spectrophotometer. The results indicate that a set of 16 discrete wavelengths is sufficient to represent the absorbance and reflectance of the samples in the 400 – 800 nm range. This facilitates the detection (when integrated into a diagnostic device), and achieved a better limit of detection (LoD: 12 parasites/µL of RBC) when compared with microscopy or RDTs (LoD: 50-200 parasites/µL of RBC), and potentially disease quantification and stage differentiation. Additionally, we validated the designed microsystem by measuring the transmittance detection of healthy and P. falciparum-infected RBCs with 12, 25 and 50 parasites/µL. Overall, our study demonstrated that the sensitivity of spectrophotometry is competitive to the one of the conventional diagnostic methods, affirming its potential for malaria diagnosis. Furthermore, the integration of these low-cost, non-invasive, and rapid diagnostic device addresses the escalating clinical demands for improving malaria diagnosis and elimination.